(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Literary style is the distinctive way authors craft their works, encompassing the use of language, narrative techniques, and aesthetic choices that reflect their individuality and artistic intent. Rooted in elements such as diction, syntax, tone, figurative language, and rhythm, style serves as the bridge between content and expression, shaping how readers perceive and experience a text. While some authors cultivate a recognizable signature style, others adapt their approach to suit different genres, audiences, or themes. This adaptability highlights the dynamic nature of style as a tool for both personal expression and cultural engagement. Literary style also intersects with broader literary movements and traditions, reflecting the historical, social, and philosophical contexts in which a work is created. By analysing an author’s style, readers gain deeper insights into their worldview, creative processes, and the work’s broader literary significance. This exploration of style underscores its pivotal role in defining the identity and enduring impact of literary texts, fuller understanding of their creative processes, perspective, and the work’s literary significance on a larger scale. This examination of style emphasizes how crucial it is to establish lasting influence of literary works.